Is High-dose Radiation Therapy Associated With Early Revision Due to Aseptic Loosening in Patients With a Sarcoma of the Lower Extremities Reconstructed With a Cemented Endoprosthesis?. Issue 3 (17th March 2023) - Arnold, Michael T.; Geiger, Erik J.; Hart, Christopher; Greig, Danielle; Trikha, Rishi; Sekimura, Troy; Eckardt, Jeffrey J.; Bernthal, Nicholas M.
Abstract: Background: The durability of endoprostheses after limb salvage surgery is influenced by surgical factors (resection length, implant location, and residual bone quality), implant design (modular versus custom design, rotating versus fixed hinge, coating, collars, and the use of cross pins), and host factors (patient's immune status, activity levels, and age). In general, radiation therapy increases the risk of fractures, infection, delayed wound healing, and impaired osseointegration. Several studies have shown exposure to radiation to be associated with higher endoprosthesis revision rates and higher periprosthetic infection rates, but results are inconsistent. Although radiation therapy is not routinely used in the treatment of many bone sarcomas in current practice, it is still used in high doses after resection and prosthetic reconstruction in patients who have Ewing sarcoma with close or positive margins and in patients with soft tissue sarcoma. It is also used in varying doses after prosthetic reconstruction in patients with myeloma or bone metastasis after resection of periarticular destructive tumors. These patients may be at an increased risk of complications due to their radiation exposure, but this is a difficult question to study given the rarity of these diagnoses and poor overall survival of these patients. We therefore leveraged a large, longitudinally collected, 40-year endoprosthesis database that included patients who received radiation to the extremity for many bone and soft tissue sarcomas to investigate the association between preoperative or postoperative radiation therapy and endoprosthesis survival. Questions/purposes: (1) Is receiving preoperative or postoperative radiation therapy in low or high doses for the treatment of bone or soft tissue malignancy of the lower extremities associated with decreased implant survivorship free from amputation or revision due to any cause? (2) Is receiving preoperative or postoperative radiation therapy in low or high doses for the treatment of bone or soft tissue malignancy of the lower extremities associated with decreased implant survivorship free from revision specifically due to aseptic loosening? (3) Is receiving preoperative or postoperative radiation therapy for the treatment of Ewing sarcoma of the femur specifically associated with decreased implant survivorship free from revision specifically due to aseptic loosening? Methods: This was a retrospective, comparative study using our institution's database of 822 endoprostheses. Between 1980 and 2019, we treated 541 patients with primary cemented endoprostheses of the extremities. Of those patients, 8% (45 of 541) were excluded due to unknown radiation status, 3% (17 of 541) because of prior failed allograft, 15% (83 of 541) due to metastatic disease from a carcinoma, 1% (6 of 541) due to a nononcologic diagnosis, 4% (20 of 541) due to benign tumor diagnosis, 16% (87 of 541) due to upper extremity tumor location, 9% (49 of 541) due to not receiving chemotherapy, and 3% (14 of 541) due to expandable prostheses. Of the remaining 220 patients, 6% (13) were considered missing because they did not have 2 years of follow-up and did not reach a study endpoint. No patients had surgery within the last 2 years of the study end date. In all, 207 patients met inclusion criteria and were eligible for analysis. Patients who had received radiation to the lower extremities at any point in their treatment course were included in the radiation group and were compared with patients who did not receive radiation. For patients where radiation dose was available, the radiation group was subdivided into a low-dose (≤ 3000 cGy) and high-dose (> 3000 cGy) group. Revision surgery was defined as any surgery necessitating removal or replacement of the tibial or femoral stem. The complications necessitating revision or amputation were poor wound healing, aseptic loosening, implant breakage, deep infection, and tumor progression. The primary outcome of interest was implant survival free from revision or amputation due to any cause. The secondary outcome of interest was implant survival free from revision or amputation specifically due to aseptic loosening. The Kaplan-Meier survivorship curves were generated with implant survival free from revision or amputation as the endpoint and patient death as a competing risk. A log-rank test was used to identify differences in survivorship between the patients who received radiation and those who did not. Multivariate regression was used to identify factors associated with decreased implant survival. An odds ratio was used to determine relative effect size among the factors associated with decreased implant survival. Results: The mean implant survival time for patients who did not receive radiation was 18.3 years (95% confidence interval [CI] 15.4 to 21.3) whereas the mean implant survival time for patients who received low- and high-dose radiation were 19.1 years (95% CI 14.5 to 23.7; p = 0.59) and 13.8 years (95% CI 8.2 to 19.5; p = 0.65), respectively. The mean implant survival free from revision for aseptic loosening for patients who did not receive radiation was 27.1 years (95% CI 24.1 to 30.1) whereas the mean implant survival for patients who received low- and high-dose radiation were 24.1 years (95% CI 19.1 to 29.1; p = 0.34) and 16.4 years (95% CI 10.6 to 22.2; p = 0.01), respectively. Patients who received high-dose radiation had decreased 5-year implant survivorship free from amputation or revision due to aseptic loosening (73% [95% CI 44% to 89%]) compared with patients who did not receive radiation (95% [95% CI 90% to 99%]; p = 0.01). For patients treated for Ewing sarcoma of the femur, the 5-year implant survival free from amputation or revision due to aseptic loosening for patients who did not receive radiation (100% [95% CI 100% to 100%]) was no different compared with patients who received radiation (71% [95% CI 35% to 90%]; p = 0.56). Conclusion: The results of this study may apply to scenarios where radiation is used, such as Ewing sarcoma with positive margins or local recurrence and after prosthetic reconstruction in patients with myeloma or bone metastasis after resection of periarticular destructive tumors. Surgeons may consider closer monitoring for early clinical and radiographic signs of aseptic loosening in patients who received high-dose radiation. These patients may also benefit from constructs that have increased resistance to aseptic loosening such as cross-pin or side plate fixation. The association between radiation and aseptic loosening should be further studied with larger studies with homogeneity in tumor diagnosis and prosthesis. The dose-dependent relationship between radiation and bone-related complications may also benefit from controlled, laboratory-based biomechanical studies. Level of Evidence: Level III, therapeutic study.